2022
DOI: 10.1155/2022/8775989
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bulbification of Five Lily Varieties: An Effective Method to Produce Quality Seeds and Flowers

Abstract: Lilies are one of the most important, beautiful, and economically valuable flowers in the world. Lilium is regarded as a popular floral trade cut flower, so viable protocols are needed to provide seed production, multiplication, and preservation. In vitro protocols allow for rapid large-scale production and rejuvenation of planting material, but to be a commercially viable multiplication method, the procedure must allow for rapid production of viable, true-to-type plants quickly. The objective was to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…According to (Pandey, Singh, & Mamta Sharma, 2009), maximum proliferation has been recorded by micropropagation of Lilium using bulb scales as explants cultivated on MS medium supplemented with 0.50 mg/1 NAA and 2.0 mg/1 BAP. The Lilium "Batavus" and Lilium "Hyde Park" varieties exhibited better in vitro responses, especially when grown with 1.0 and 1.5 mg L1 BAP (Lapiz-Culqui et al, 2022). In the present study, different concentrations of IAA, NAA, or IBA-supplemented MS medium were utilized to promote root development.…”
Section: Discussionmentioning
confidence: 91%
“…According to (Pandey, Singh, & Mamta Sharma, 2009), maximum proliferation has been recorded by micropropagation of Lilium using bulb scales as explants cultivated on MS medium supplemented with 0.50 mg/1 NAA and 2.0 mg/1 BAP. The Lilium "Batavus" and Lilium "Hyde Park" varieties exhibited better in vitro responses, especially when grown with 1.0 and 1.5 mg L1 BAP (Lapiz-Culqui et al, 2022). In the present study, different concentrations of IAA, NAA, or IBA-supplemented MS medium were utilized to promote root development.…”
Section: Discussionmentioning
confidence: 91%
“…They also found that the explant survival rate of basal scales was higher than that of tip bulb scales. Lapiz-Culqui et al [136] and Patil et al [137] used the bulb scales to cultivate different Lilium cultivars. Youssef et al [138] used the leaf as an explant in their study to increase Lilium bulb number and size.…”
Section: Stage 1: Establishment Of Aseptic Culturementioning
confidence: 99%
“…They also found that the explant survival rate of basal scales was higher than the tip bulb scales. Lapiz-Culqui, et al [124] and Patil, et al [125] used the bulb scales to cultivate different Lilium cultivars. Youssef, et al [126] used the leaf as explant in their study to increase Lilium bulb number and size.…”
Section: Stage 1: Establishment Of Aseptic Culturementioning
confidence: 99%